Botswana Open Repositories Role In Sdgs Research Based Knowledge Sharing Process: A Bibliometric Analysis - Kassahun, Kelemwork Agafari (My University, 2023)
Description The United Nations (UN) sustainable development goals (SDGs), adopted in September 2015, are a global socioeconomic agenda that calls for collective action to achieve peace, prosperity, and well-being by 2030. The 17 goals and 169 targets of the SDGs were developed to succeed the eight Millennium Development Goals (MDGs), which ended in 2015 UNESCO (2021) At least 10 of the 17 Sustainable Development Goals (SDGs) comprising the 2030 Agenda for Sustainable Development require constant scientific research. Scientific research knowledge has to share with respective research stakeholders. Open-access repositories facilitate access to scientific research (Sweileh,2020). Based on this fact, this study would like to examine the contribution of Botswana universities' repositories in promoting SDGs research practices to the scientific community and citizen scientists. The study will apply a descriptive bibliometric analysis by reviewing research publications on SDG from 2015 to 2022 from three Botswana universities' institutional repository collections. The bibliometric analysis will be conducted in three steps. The information will be searched and retrieved from three universities' institutional repositories ( University of Botswana, Botho University and Botswana International University of Science and Technology. The data will be retrieved by searching ("SUSTAIN ABLE DEVELOPMENT GOAL*" or "SDG*") in the field "TITLE" or Abstract.
Keywords: SDGs; Open Repositories; Sustainable Development